Rho-associated protein kinase and cyclophilin a are involved in inorganic phosphate-induced calcification signaling in vascular smooth muscle cells - Tatsuya Tsuda; Masaki Imanishi; Mizuho Oogoshi; Mitsuhiro Goda; Yoshitaka Kihira; Yuya Horinouchi; Yoshito Zamami; Keisuke Ishizawa; Yasumasa Ikeda; Ichiro Hashimoto; Toshiaki Tamaki; Yuki Izawa-Ishizawa (Elsevier, 2020)
Arterial calcification, a risk factor of cardiovascular events, develops with differentiation of vascular smooth muscle cells (VSMCs) into osteoblast-like cells. Cyclophilin A (CypA) is a peptidyl-prolyl isomerase involved in cardiovascular diseases such as atherosclerosis and aortic aneurysms, and rho-associated protein kinase (ROCK) is involved in the pathogenesis of vascular calcification. CypA is secreted in a ROCK activity-dependent manner and works as a mitogen via autocrine or paracrine mechanisms in VSMCs. We examined the involvement of the ROCK-CypA axis in VSMC calcification induced by inorganic phosphate (Pi), a potent cell mineralization initiator. We found that Pi stimulated ROCK activity, CypA secretion, extracellular signal-regulated protein kinase (ERK) 1/2 phosphorylation, and runt-related transcription factor 2 expression, resulting in calcium accumulation in rat aortic smooth muscle cells (RASMCs). The ROCK inhibitor Y-27632 significantly suppressed Pi-induced CypA secretion, ERK1/2 phosphorylation, and calcium accumulation. Recombinant CypA was found to be associated with increased calcium accumulation in RASMCs. Based on these results, we suggest that autocrine CypA is mediated by ROCK activity and is involved in Pi-induced ERK1/2 phosphorylation following calcification signaling in RASMCs. Keywords: Arterial calcification, Cyclophilin A, Rho-associated protein kinase, Vascular smooth muscle cell, Atherosclerosis